Dynamický Balanced Scorecard v učící se organizaci - Leciánová, Gabriela (2007)
The main goal and intended contribution of the presented doctoral dissertation is to define the most important principles for the usage of the Dynamic Balanced Scorecard (DBSC) as a practical guide for learning organization. The Dynamic Balanced Scorecard is based on the fundamental idea that the conventional (static) Balanced Scorecard (BSC) is not able to encompass the contemporary dynamic environment and hence is not an appropriate tool for any strategic management system. At the beginning of the dissertation, the thesis is dedicated to description of the BSC limitations. Moving further, the thesis establishes a practical guide described in three stages:  the main principles of DBSC,  the methodology of implementing DBSC,  the working model. The model was developed in a real company and is now being used in pilot operation. Furthermore the model contains measurements that help demonstrate the transformation from a traditional organization to a learning organization. I did not find, based on questionnaires collected from 110 companies and my experience in a consulting company, any examples of DBSC being currently used in the Czech Republic. The original hypothesis about non-use of any dynamic model for strategic management system was confirmed in the empirical part of the dissertation